2020
DOI: 10.1017/s1368980019004397
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary total antioxidant capacity and breast cancer: a case–control study in a Middle Eastern country

Abstract: Objective: The aim of this study was to determine the relationship between dietary total antioxidant capacity (dTAC) and risk of breast cancer among Iranian women. Design: In this hospital-based case–control study, dietary intake of participants was collected using a 168-item validated FFQ. Dietary TAC was assessed using FRAP assay considering. Logistic regression was used to obtain ORs for breast cancer across quartiles of dTAC. Setting: Cancer Institute, Iran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The association of these nutrients with BC risk has been suggested in several studies [40][41][42][43]. Furthermore, this dietary pattern is high in dietary antioxidants such as proanthocyanidines, avonoids, stilbenes and alpha-tocopherols [44,39] which could reduce cancer risk [45][46][47]. Moreover, it is associated with lower circulating C-reactive protein which could explain the anti-in ammatory effect of this diet [48,49].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The association of these nutrients with BC risk has been suggested in several studies [40][41][42][43]. Furthermore, this dietary pattern is high in dietary antioxidants such as proanthocyanidines, avonoids, stilbenes and alpha-tocopherols [44,39] which could reduce cancer risk [45][46][47]. Moreover, it is associated with lower circulating C-reactive protein which could explain the anti-in ammatory effect of this diet [48,49].…”
Section: Discussionmentioning
confidence: 97%
“…Decreased in ammation and enhanced antioxidant capacity of the body could suppress cell proliferation, spontaneous mutation and DNA methylation, all of which may lead to reduced cancer incidence. [47,50] The DASH dietary pattern insists on higher intake of ber and lower intake of simple carbohydrates, both of which are associated with lower glycemic index. It could therefore decrease the circulating level of insulin and insulin-like growth factor 1, which are associated with an elevated risk of ontogenesis [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not examine the validity of this questionnaire for assessment of dietary TAC. However, earlier publications based on this questionnaire have revealed that data on dietary TAC from this questionnaire can be used to predict the chronic conditions ( 36 ). Moreover, some components of DDS and AHEI including corn flakes and alcohol consumption were not considered in this study, because of the lack of data in the original data set.…”
Section: Discussionmentioning
confidence: 99%
“…Among cancers, breast cancer is suggested as a serious female malignant tumor with a high incidence in the world (Siegel et al., 2016). Epidemiological studies have shown that increased intake of fruits, vegetables, and whole grains have provided a significant inverse association with breast cancer (Karimi et al., 2014; Marzbani et al., 2019; Rigi et al., 2021; Sasanfar et al., 2021). Frequent consumption of functional foods, fresh fruits, and vegetables is an effective way to reduce the incidence of various cancers and improve the quality of life of patients (Joshipura & Kaumudi, 2001).…”
Section: Resultsmentioning
confidence: 99%